Netralitas Politik Aparatur Sipil Negara dalam Perspektif Perlindungan Hak Asasi Manusia - Muhammad Riora; Ulya Kencana; Kun Budianto (Wajah Hukum, 2020)
In the legal and governmental aspects, bureaucratic reform is very urgent to be realized, including the policy of ASN political neutrality. Therefore, this study aims to analyze the political neutrality policy of ASN according to Law Number 5 of 2014 concerning State Civil Servants in the Perspective of Human Rights Protection. The scope of this research is carried out by drawing legal principles against written positive law. Legal principles are used in interpreting Law Number 5 of 2014 concerning ASN by relating it to the perspective of protecting human rights. The method used is normative juridical legal research using secondary data. The research results reveal that every civil servant organization does not take sides with any form of influence and interests of anyone. In this case, there are restrictions on the political rights of ASN according to Law Number 5 of 2014 concerning State Civil Servants not violating human rights as stipulated in the 1945 Constitution of the Republic of Indonesia. According to the principles of Islamic law, ASN must be neutral and obedient to leaders. Elected without antagonizing him. Thus, it is concluded that the ASN political neutrality policy has met 4 indicators of a rule of law, namely protection of human rights, distribution of power, governance based on laws and regulations, and state administrative court.